Pemanfaatan Ansible dalam Sistem Otomatisasi Dan Monitoring Jaringan Komputer - Tivvany Aijen, Loudry; indahsari, rina dewi (JURNAL SISTEM KOMPUTER ASIA, 2023)
Installed network devices may require reconfiguration to continue functioning properly. Enterprises still use manual configuration methods when configuring network devices. With large numbers of devices, manual configuration can be time-consuming, highly complex, and prone to human error. A more efficient way to automatically configure these devices is network automation. Network automation is a system created for configuring multiple routers simultaneously. Installed network devices may require reconfiguration to continue functioning properly. Enterprises still use manual configuration methods when configuring network devices. With large numbers of devices, manual configuration can be time-consuming, highly complex, and prone to human error. A more efficient way to automatically configure these devices is network automation. Network automation is a system created for configuring multiple routers simultaneously. The results are tested in a network simulation application or GNS3. Configuration automation is implemented by an Ansible script that connects to the router via Secure Shell (SSH) so that the configuration can be entered into the router. The routers used in this study are virtual routers created with GNS3. As a result of this research, we have successfully used Ansible to automate router configuration. Regardless of the routers installed in your network, routers can only be automated using scripts written in Ansible. Applying network automation facilitates the automatic configuration of large-scale network devices, minimizing human error.